Phylogenetic and morphological characterization of Chlorella pyrenoidosa from the Java Sea, Indonesia - ELYA PUTRI PANE; YENNY RISJANI; YUNIANTA YUNIANTA; ZAKARIA BELGHOUL; KURNIA RAHMAWATI; GILANG DRAJAT MAULANA; RYAN NUGRAHA (Society for Indonesian Biodiversity, 2025)
Abstract. Pane EP, Risjani Y, Yunianta, Belghoul Z, Rahmawati K, Maulana GD, Nugraha R. 2025. Phylogenetic and morphological characterization of Chlorella pyrenoidosa from the Java Sea, Indonesia. Biodiversitas 26: 3061-3070. Pathek Beach in Situbondo, East Java, Indonesia, is a site of particular interest due to its richness in marine biodiversity and offers promising sites for microalgal bioprospecting. This beach is distinguished by its dark sand and natural rock wave breakers, contributing to its unique geomorphological features. This study explores and identifies green microalgae, specifically a strain suspected as Chlorella pyrenoidosa, namely UB02 PATHEK PSAL. This strain is part of the microalgae collection maintained by the Research Center on Algae and Environment (ALGAEN), where it was maintained after being isolated from the Pathek coastal area. The isolation phase of this study utilized capillary techniques for the specific morphological identification of the microalgae strain. Single-cell isolation was achieved using a capillary micropipette technique under the Olympus IX 53 inverted microscope, followed by cultivation in sterile F/2 Walne medium. The study objective was to describe the morphology features using light microscopy and Scanning Electron Microscopy (SEM) and conduct molecular identification using the rbcL gene to confirm the species identity. The rbcL gene was selected as a reliable molecular marker for low-level plant phylogenetics in this study due to its effectiveness in analyzing evolutionary relationships across different taxonomic groups. The isolated strain's genetic material was sequenced, and a comparative analysis was performed using the Basic Local Alignment Search Tool (BLAST) from the National Center for Biotechnology Information (NCBI). The results revealed a 99.48% similarity with known C. pyrenoidosa strains, specifically Wu-G3H3-1-2 and strain 820, confirming the species identity. This research enhances understanding of the biodiversity of East Java's marine ecosystems and highlights the potential for discovering new microalgae species, sparking excitement and hope for future discoveries. C. pyrenoidosa is widely recognized for its highly nutritional and bioactive compounds, including lipid and protein, which are valuable for use in biofuel production and functional foods, and pharmaceuticals.